Mangan tamu Kapampangan culinary heritage repository and food school - Partolin, Christopher III S.; Dimanlig, Horacio Evelio C. (2010)
The province of Pampanga has always been regarded as gourmet province of the Philippines. It boasts a wide array of culinary history and tradition which is passed from one Kapampangan generation to another. Kapampangan cuisine is said to be one of the most refined and sophisticated Philippine foods. Throughout the years, t he Kapampangans has been famous for their delectable foods and old-style cooking practices. Angeles City in particular is home to the first culinary museum in the country called the "Culinarium". It showcases the long history of Kapampangan cuisine which also tells the story of the ladies of the province serving the official of the church particularly the friars. However, despite of all the years of recognizing as the culinary center of the country, Pampanga still doesn't have any formal and centralized culinary institution that would cater the minds of food Kapampangan food experts and enthusiasts as well as Filipino food lovers about the arts and science of food preparation. This research is all about developing a self-sustaining culinary institution and a public park which serves as repository of Kapampangan culinary heritage. It introduces new trends in full advantage of the view of the landscape while preparing food. Part I describes the nature of the research, making clear the problem which the researcher needs to find solution to. Part II is about thorough analysis of the site and studies on the viability of the project. Part III gives the researcher's solution to the stated problem and how these solutions are translated into a landscape design.
Vita.
Thesis (Bachelor of Landscape Architecture)--University of the Philippines, Diliman.
Keywords: Culinary center -- Design; Culinary heritage facility -- Design